2021
DOI: 10.1111/agec.12681
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic effects of price support policy on price volatility: The case of the rice market in China

Abstract: This study examines the economic and welfare effects of a commodity price support policy. It conceptually and empirically evaluates the effects of the domestic pricing policy on the distribution of commodity prices, with an application to the price support program in the Chinese rice market. The empirical analysis relies on a Censored Quantile Autoregression (CQAR) model, which provides a refined and flexible representation of the evolving distribution of prices under a price support program. Based on monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…For every 1% increase in soybean price, the planting area will increase by 1.650%, and the per unit yield will decrease by 0.898%. Farmers' production is usually blind [60,61], and when the price of a certain agricultural product rises, producers will weigh the benefits they can obtain from the production of various crops, and their land use decisions will be affected by price changes [62], but different crops have slightly different degrees of response [63][64][65]. In addition, studies have demonstrated that the education level and planting experience of farmers have a significant positive impact on crop yield [66,67]; while soybean prices rise, many farmers with less planting experience expand the planting area, resulting in low yield per unit area of the newly added area, thus lower overall soybean yields.…”
Section: Impact Of Soybean Price On Soybean Productionmentioning
confidence: 99%
“…For every 1% increase in soybean price, the planting area will increase by 1.650%, and the per unit yield will decrease by 0.898%. Farmers' production is usually blind [60,61], and when the price of a certain agricultural product rises, producers will weigh the benefits they can obtain from the production of various crops, and their land use decisions will be affected by price changes [62], but different crops have slightly different degrees of response [63][64][65]. In addition, studies have demonstrated that the education level and planting experience of farmers have a significant positive impact on crop yield [66,67]; while soybean prices rise, many farmers with less planting experience expand the planting area, resulting in low yield per unit area of the newly added area, thus lower overall soybean yields.…”
Section: Impact Of Soybean Price On Soybean Productionmentioning
confidence: 99%
“…Yet there is not a single liquidity proxy that is proved to be universally suitable and accepted, since the effectiveness of liquidity proxies might be somehow marketand country-specific. Therefore, it is an empirical issue for researchers to find out which proxy works well in specific markets, the efforts of which have been made to bond markets Liquidity of China's futures market (Goyenko and Ukhov, 2009), stock markets (Corwin and Schultz, 2012;Fong et al, 2017) and commodity markets (Ferguson and Mann, 2001;Frank and Garcia, 2011;Marshall et al, 2012;Li et al, 2021). With the rapid growth of production, consumption and trade of agricultural commodities in China, the extant literature has paid an increasing attention to the performance of Chinese commodity futures markets, including price transmission (Wen and Wang, 2004;Wang and Ke, 2005;Xu et al, 2019), intraday trading (Liu et al, 2016;Xu et al, 2018) and liquidity premium (Hung et al, 2015;Li et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The comprehensive effect of the price support policies has attracted extensive attention from academics and policymakers. Many studies have investigated the impacts of price support policies on farm income and welfare (Beghin et al, 2003;Jayne et al, 2008;Lichtenberg & Zilberman, 1986;Li et al, 2021;Miranda & Helmberger, 1988;Mu & Koike, 2009;Otsuka & Hayami, 1985;Qian et al, 2020;Zhao et al, 2017); food security (Qian et al, 2020); and output and productivity (Lu, 2002;Mu & Koike, 2009). The price stabilization and enhancement effects of the price support policy have drawn the attention of economists and policymakers as well (Gouel, 2013;Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the impacts of price support policies on farm income and welfare (Beghin et al, 2003;Jayne et al, 2008;Lichtenberg & Zilberman, 1986;Li et al, 2021;Miranda & Helmberger, 1988;Mu & Koike, 2009;Otsuka & Hayami, 1985;Qian et al, 2020;Zhao et al, 2017); food security (Qian et al, 2020); and output and productivity (Lu, 2002;Mu & Koike, 2009). The price stabilization and enhancement effects of the price support policy have drawn the attention of economists and policymakers as well (Gouel, 2013;Li et al, 2021). The effect of price stabilization aids in lowering the volatility of market prices (Jayne et al, 2008;Kim & Chavas, 2002;Li et al, 2021;Miranda & Helmberger, 1988;Qian et al, 2013;Wang & Li, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation